AB0639 Risk of mortality in sjogren's syndrome after 1st admission. (12th June 2018) - Chen, Y.-C.
Abstract : Background: The long-term prognosis of patients with SS is unclear. Population-based studies have shown conflicting evidence regarding relative mortality in SS. Objectives: There is conflicting evidence regarding prognosis in patients with SS (pSS). The aim of this study was to estimate the risk factors of mortality in patients with SS through a in hospital review. Methods: Through a review of databases through October 2002 till 2016, we identified cohort studies reporting relative risk (compared with standardised population), risk factors and causes of mortality in patients with SS. Results: We identified 695 (83.2% females) with SS, of whom 88 patients died over a median average follow-up of 13 years. Leading causes of mortality were infections; Risk factors associated with increased mortality were advanced age at diagnosis [HR 1.045 (95% CI 1.024, 1.067], male sex [RR 2.18 (95% CI 1.45, 3.27)], associated with SLE [HR 2.448 (95% CI 1.108, 5.406)], diabetes [HR 1.986 (95% CI 1.125, 3.505)] Conclusions: After first admission, the risk factor for mortality include old age, associated with SLE and diabetes. These require close follow-up. Reference: [1] Baldini C, Pepe P, Quartuccio L, et al. Primary Sjogren's syndrome as a multi-organ disease: impact of the serological profile on the clinical presentation of the disease in a large cohort of Italian patients. Rheumatology2014;53 Acknowledgements: We thanks to Kaohsiung CGMH for data support Disclosure of Interest: None declared